Human T-cell Leukemia Virus Type 1 Basic Leucine Zipper Factor (HBZ) Interacts and Inhibits the Acetyltransferase Activity of Multiple Cellular Coactivator Families to Deregulate Transcription - Wright, Diana Grace (East Carolina University)
Of the 20 million individuals infected worldwide with the complex retrovirus, Human T-cell Leukemia Virus Type 1, 5% will develop an incurable and fatal form of leukemia known as adult T-cell leukemia (ATL). During the course of infection, the promoter responsible for genome replication and expression of most viral genes is often inactivated by DNA methylation, mutation and deletion. The only gene expressed in the malignant cells is the hbz gene, which contains the open reading frame for HTLV-1 basic leucine zipper (bZIP) factor (HBZ). HBZ is regulated by a unique promoter which is unaffected by modifications. The observation that HBZ is persistently expressed and the fact that transgenic mice expressing HBZ develop symptoms similar to ATL suggest that HBZ is involved in ATL development. HBZ interacts with the homologous cellular coactivators, p300 and CBP. These proteins contain a histone acetyl transferase (HAT) domain that mediates transfer of acetyl groups from acetyl-coenzyme A to lysine residue. p300/CBP acetylate specific lysines on histones to increase transcription. These coactivators also acetylate transcription factors to modulate, among other functions, their DNA binding capacity. We found that the bZIP domain of HBZ interacts directly with the HAT domain of p300/CBP. This interaction has for consequence to inhibit acetylation of histone H3 and of the NF-kB transcription factor, p65. Inhibition of p65 acetylation leads to a decrease of its transcriptional activity. Because the transcriptional activity of the tumor suppressor p53 is also dependent on acetylation, we analyzed the effect of HBZ on this protein. We found that inhibition of p300/CBP HAT activity by HBZ reduces the acetylation of p53, which is modified following DNA damage. We also observed that HBZ interacts with HBO1, which is a HAT protein in the MYST family that acts as a transcriptional coactivator for p53. The fact that HBZ inhibits both p300/CBP and HBO1 HAT activity is correlated with a reduction of CDKN1A/p21 activation by p53. Consequently, we observed a delay in the cell cycle arrest after DNA damage in cells expressing HBZ. We propose that HBZ, by interacting with cellular coactivators and disrupting their HAT activities, could promote ATL development.
Keywords: Molecular biology; Virology; Microbiology; Acetyltransferase; Adult T-cell leukemia; HBZ; P300/CBP; Transcription; Human T-lymphotropic virus 1; Basic-Leucine Zipper Transcription Factors; Acetyltransferases; Leucine Zippers